2020
DOI: 10.1371/journal.pntd.0007972
|View full text |Cite
|
Sign up to set email alerts
|

Language and beliefs in relation to noma: a qualitative study, northwest Nigeria

Abstract: Background Noma is an orofacial gangrene that rapidly disintegrates the tissues of the face. Little is known about noma, as most patients live in underserved and inaccessible regions. We aimed to assess the descriptive language used and beliefs around noma, at the Noma Children's Hospital in Sokoto, Nigeria. Findings will be used to inform prevention programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 33 publications
0
21
0
Order By: Relevance
“…In Zambia, the disease has been labelled as ‘aka popo’, meaning the child has been fed a stillborn fetus, and the flesh is ‘coming out’ (describing the sloughing of the cheek) [ 15 ]. In Hausa, the most widely spoken language in northwest Nigeria, several names for noma have been documented including ‘ciwon iska’, ‘bakin kare’ [ 5 ], ‘danhurawa’, ‘tuareg’, ‘akin’ [ 16 ], ‘gaude’ and ‘sadde’ [ 17 ]. Several of these names are generalised terms and have reportedly caused confusion in patient recruitment drives for surgical interventions, as patients with ailments such as cleft lip and palate also identify with these names[ 5 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In Zambia, the disease has been labelled as ‘aka popo’, meaning the child has been fed a stillborn fetus, and the flesh is ‘coming out’ (describing the sloughing of the cheek) [ 15 ]. In Hausa, the most widely spoken language in northwest Nigeria, several names for noma have been documented including ‘ciwon iska’, ‘bakin kare’ [ 5 ], ‘danhurawa’, ‘tuareg’, ‘akin’ [ 16 ], ‘gaude’ and ‘sadde’ [ 17 ]. Several of these names are generalised terms and have reportedly caused confusion in patient recruitment drives for surgical interventions, as patients with ailments such as cleft lip and palate also identify with these names[ 5 ].…”
Section: Resultsmentioning
confidence: 99%
“…Several of these names are generalised terms and have reportedly caused confusion in patient recruitment drives for surgical interventions, as patients with ailments such as cleft lip and palate also identify with these names[ 5 ]. A further complicating etymological factor in the setting is that the word ‘noma’ means ‘farming’ in Hausa [ 16 ]. Names form a part of the understanding of the disease, and in this case, the beliefs about the causes of noma such as spirits, living creatures (insects and animals), and connections with previous illness [ 16 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…43 The language used to name and describe noma has been found to differ between caretakers and health care providers, which can lead to confusion and poor awareness. 44 Traditional healer treatment often involves a remedy using tree branches, herbs, and bark that is soaked for ingestion or grinded as a rub or a hot blade placed on areas of swelling to "burst the swelling," among other methods. 42 Both ensuring traditional healers can recognize early stages of noma with referral to appropriate medical institutions and developing increased partnerships with traditional healers to ensure efficient access to treatment for noma patients are essential for optimal patient outcomes.…”
Section: Psychosocial and Cultural Impactmentioning
confidence: 99%
“…Despite the major developments in health research since noma was first reported (by Hippocrates (460 to 370 BC) [ 5 ]), the disease remains poorly understood in the global health community [ 5 ]. The majority of research on noma are case reports, and there are several major gaps in knowledge, including a lack of understanding of the burden, distribution, community-level mortality rate, and aetiology of the disease [ 5 ]. Noma is a difficult disease to study due to its rapid progression, reported high mortality rate, and the remote location of affected patients [ 1 ].…”
Section: Introductionmentioning
confidence: 99%